2015
DOI: 10.12659/aot.893549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bile Colonization and Intestinal Flora may Improve Management in Liver Transplant Recipients Undergoing ERCP

Abstract: Background:Immunosuppression, denervation of biliary tract, and presence of biliary strictures favor colonization of bile with microorganisms after liver transplantation. Little is known about spectrum and antibiotic susceptibility of this colonization. Material/Methods:Bile and feces were collected prospectively from 38 patients who underwent endoscopic retrograde cholangiopancreaticography after liver transplantation. Samples were analyzed for colonization and antibiotic susceptibility. Results:From the 38 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Several studies have identified LT as a risk factor for increasing microbial colonization of bile. In these studies, an increased incidence of gram-positive bacteria with increasing antibiotic resistance, such as enterococci and Candida species, in patients with LT was found[26-29]. In our study, we found a remarkably high prevalence of Candida species (39.1%), whereas the prevalence of enterococci was 29.7%.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have identified LT as a risk factor for increasing microbial colonization of bile. In these studies, an increased incidence of gram-positive bacteria with increasing antibiotic resistance, such as enterococci and Candida species, in patients with LT was found[26-29]. In our study, we found a remarkably high prevalence of Candida species (39.1%), whereas the prevalence of enterococci was 29.7%.…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, colonization by enteric bacteria, despite successful endoscopic treatment, and fungibilia were associated with lower retransplantation-free survival. Later, the composition of the bile microbiome by was confirmed culture-based techniques by a smaller prospective study [144]. Only in the studies by Liu et al [145,146] was the bile microbiota assessed by 16S-rRNA gene sequencing.…”
Section: Faecalibacterium Lachnospiramentioning
confidence: 92%
“…Finally, only a handful of studies has evaluated the composition of the bile microbiome in LT recipients, exclusively in patients undergoing ERCP/percutaneous transhepatic cholangiography for biliary complications [144]. In a prospective cohort of 213 patients, the authors showed that the most common bacterial isolates were Enterococcus spp.…”
Section: Faecalibacterium Lachnospiramentioning
confidence: 99%
“…[19][20][21] Gram-positive bacterial infection has attracted attention recently because it is highly detected in cholangitis of liver transplantation patients. [22][23][24] Mohammed et al showed that the consequences of bacteriobilia can be prevented by pre-operative and postoperative antibiotics that act on the common digestive tract pathogens such as enterobacters and anaerobes. 25 Also, Herzog et al recommended bile cultures during biliary surgeries for better antibiotic sensitivity and prophylaxis from infective complications.…”
Section: Introductionmentioning
confidence: 99%
“…are the most commonly observed gram‐positive microorganisms 19–21 . Gram‐positive bacterial infection has attracted attention recently because it is highly detected in cholangitis of liver transplantation patients 22–24 . Mohammed et al .…”
Section: Introductionmentioning
confidence: 99%